2008
DOI: 10.1590/s1984-29612008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Recuperação de larvas infectantes de Trichostrongylus colubriformis em três espécies de gramíneas contaminadas no verão

Abstract: RESUMOO experimento teve como objetivo avaliar a recuperação de larvas infectantes (L3) de Trichostrongylus colubriformis em Brachiaria decumbens cv. Australiana, Cynodon dactilon cv. Coast-cross e Panicum maximum cv. Aruana. Foram utilizados módulos experimentais constituídos por seis canteiros de 32,4 m 2 cada, perfazendo dois canteiros por espécie forrageira.Cada canteiro foi dividido em 36 parcelas, de 30 x 30 cm, de forma a permitir seis repetições por espécie e por altura da forragem em cada semana de co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
1
17
0
6
Order By: Relevance
“…Carneiro and Amarante (2008), in a study carried out in the same site of the present experiment, also observed higher recovery of H. contortus L3 from 30 cm high Aruana herbage at the moment of contamination. Rocha et al (2008), however, did not find influence of the herbage height on the recovery of T. colubriformis L3 in the summer. Such results indicate that the variation in the climate conditions may change the migration of gastrointestinal nematodes.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Carneiro and Amarante (2008), in a study carried out in the same site of the present experiment, also observed higher recovery of H. contortus L3 from 30 cm high Aruana herbage at the moment of contamination. Rocha et al (2008), however, did not find influence of the herbage height on the recovery of T. colubriformis L3 in the summer. Such results indicate that the variation in the climate conditions may change the migration of gastrointestinal nematodes.…”
Section: Discussionmentioning
confidence: 55%
“…Fecal pellets act as reservoirs of infective larvae, especially during dry periods (CARRATORE, 2004;ROCHA, 2006). However, in rainy periods, the degradation of feces is higher (ROCHA et al, 2008). Rocha et al (2008) recovered, on average, only 20%, 31.5% and 36.6% from the feces deposited among Brachiaria, Aruana and Coast-cross herbage, respectively, in the last sampling (16 weeks after deposition of feces in the summer).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations